Challenge Between Two Principles Of Truth Discovery And Dispute Resolution In The Maxims Of Criminal Courts With A Glance At Penal Laws In Iran’s Courts - خالقي, أبو الفتح; شربو, نور الدين (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Although the principles governing the laws of the criminal courts are numerous, all their systems are based on either of the two principles “truth discovery” or “dispute resolution”. It is evident that acceptance of the two or either of the two foresaid principles would emphasize on the idea that the collection of the preliminary assumptions is taken into account, on the one side, and there is a need, on the other side, for accepting the outcomes that cannot be neglected. Both of these principles can be seen in the maxims of Iran’s penal laws and their reason returns to some of their regulations that have been drawn on the Islamic Penal Code of Law. Due to the same reason, the principle in some of the crimes related to the people’s rights is the discovery of truth or resolving of the dispute along with some other issues of the secondary importance; or, the principle in some of the crimes related to the God’s rights is the resolution of the dispute and the truth discovery would be deemed as an exception.